Different environmental gradients affect different measures of snake β-diversity in the Amazon rainforests - de Fraga, Rafael; Ferrão, Miquéias; Stow, Adam J.; Magnusson, William E.; Lima, Albertina P. (PeerJ, 2018)
Mechanisms generating and maintaining biodiversity at regional scales may be evaluated by quantifying β-diversity along environmental gradients. Differences in assemblages result in biotic complementarities and redundancies among sites, which may be quantified through multi-dimensional approaches incorporating taxonomic β-diversity (TBD), functional β-diversity (FBD) and phylogenetic β-diversity (PBD). Here we test the hypothesis that snake TBD, FBD and PBD are influenced by environmental gradients, independently of geographic distance. The gradients tested are expected to affect snake assemblages indirectly, such as clay content in the soil determining primary production and height above the nearest drainage determining prey availability, or directly, such as percentage of tree cover determining availability of resting and nesting sites, and climate (temperature and precipitation) causing physiological filtering. We sampled snakes in 21 sampling plots, each covering five km2, distributed over 880 km in the central-southern Amazon Basin. We used dissimilarities between sampling sites to quantify TBD, FBD and PBD, which were response variables in multiple-linear-regression and redundancy analysis models. We show that patterns of snake community composition based on TBD, FBD and PBD are associated with environmental heterogeneity in the Amazon. Despite positive correlations between all β-diversity measures, TBD responded to different environmental gradients compared to FBD and PBD. Our findings suggest that multi-dimensional approaches are more informative for ecological studies and conservation actions compared to a single diversity measure.
Keywords: Brazil; Environmental filtering; Functional diversity; Phylogenetic diversity; Taxonomic diversity